Understanding oil : markets, prices and the revenue impact of the 1990 oil shock on Trinidad and Tobago. - John, Michael (1990)
Describes some conceptual and other issues related to markets and the petroleum market in particular, and discusses spot, contract and futures market. Raises some of the issues related to Trinidad and Tobago in an assessment of the revenue implications of the price increases since the invasion of Kuwait.